Sesame Street. A magical Halloween adventure [videorecording (DVD)] - Diego, Ken; Rhea, Caroline, 1964-; Clash, Kevin; Brill, Fran; Robinson, Martin P.; Mazzarino, Joseph; Nelson, Jerry, 1934-2012 (Sesame Street, 2004)
Halloween is a time of jack-o-lanterns, dressing up, and lots of silliness on Sesame Street. Share the surprises as they learn to carve pumpkins, make scarecrows, and discover that monsters don't really have to be scary!